Aprendizagem móvel e ensino de ciências: Um suporte para professores de ciências e biologia - Lima, Leonardo Viana de (2017)
Considering that one of the functions of Science Teaching is to provide conditions for the citizen to be able to recognize and use scientific and technological knowledge in the decisions to be made for his benefit and the society in which he lives. This research made a small cut in the teaching-learning process and reflect on Science Teaching in general, and teaching Biology in particular, with emphasis on Mobile Learning. Given the possibilities of elaborating an educational technology product could be more significant and potentially more impacting in the reality of teachers offering conditions for research inside and outside the classroom; aggregation of specific knowledge pertinent to the Teaching of Sciences and Biology process, as the conditions for oral and written communication; establishment of cooperative work among students; the exercise of authorial and critical capacity, where the organization of thought and freedom of reflection integrate the construction of knowledge. The name of the application, Science in the palm of the hand, was chosen with the intention of directly represent the objectives of the same and try to bring the universe of Science closer to the school community through mobile learning. The application is divided into 5 sections: "Brazilian scientists", "Daily life science", "Science and time", "Scientist in action" and "Science for all" and is available for download on Google Play.